Study of [Pb(II) Dicarboxylic Acids-Propylenediamine] System as a Tool in Removal of Excess Lead from Human Blood: A Polarographic Approach - Paliwal, R.K. (Asian Journal of Chemistry, 2010)
The mixed ligand complexes of propylenediamine (pn) and malonate (mal2-) or maleate (male2-), with Pb(II) have been studied polarographically at constant ionic strength, μ = 1.5 M (NaNO3) and pH 7.3 at 25.0 ± 0.1 ºC. The reduction of the complexes at d.m.e. is reversible and diffusion-controlled. One mixed complex [Pb(mal)(pn)] and [Pb(male)(pn)] is formed in each case and the stability constant at 25 ºC are log β11 = 8.99 and 8.90, respectively.